2021
DOI: 10.3390/medicina57121373
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer and Human Papillomavirus Awareness among Women in Saudi Arabia

Abstract: Background and Objectives: Cervical cancer (CC) is the eighth most common cancer among Saudi women of all ages. With limited national data, we aimed to evaluate the public awareness of cervical cancer, CC risk factors, HPV infection, and HPV vaccines in different regions of Saudi Arabia. Materials and Methods: This was a survey-based cross-sectional study that encompassed 564 Saudi women over a period of a month. A self-administrated questionnaire was distributed through different social media platforms. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
3
15
1
Order By: Relevance
“…A total of 24.5% were moderate and only 4.4% were categorized as having a good level of knowledge (mean score: 3.56; SD 2.91, out of 11 points). These findings are consistent with the literature wherein most women demonstrated a lack of understanding regarding the basic facts of HPV, infection, screening, and prevention [7][8][9][10][11][12][13]. In Aseer Region, Saudi Arabia, there has been a report that only a small proportion (17.4%) of Saudi females had good knowledge about cervical cancer [14].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A total of 24.5% were moderate and only 4.4% were categorized as having a good level of knowledge (mean score: 3.56; SD 2.91, out of 11 points). These findings are consistent with the literature wherein most women demonstrated a lack of understanding regarding the basic facts of HPV, infection, screening, and prevention [7][8][9][10][11][12][13]. In Aseer Region, Saudi Arabia, there has been a report that only a small proportion (17.4%) of Saudi females had good knowledge about cervical cancer [14].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, only 16% were aware of the condition that HPV screening should be done regularly every three years. In a study done in Riyadh, Saudi Arabia, women showed a better awareness level that HPV was transmitted sexually (78.9%), or that it caused genital warts (81.7%) and cervical cancer (81.9%) [10]. However, contradicting these reports, stating that nearly half of the subjects (49%) disagreed that HPV is a common sexually transmitted infection and only 38% agreed that all cervical cancers are caused by HPV infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding was unexpected in the context of current public awareness campaigns about the HPV virus and the inclusion of the HPV vaccine in the national immunization schedule. In Saudi Arabia, the HPV vaccine is given to females of age 9 to 13 years as part of the country's national immunization program [9,10]. Only a few percent of women knew that HPV infection was common in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is listed as one of the most common cancers in females in Saudi Arabia and has become the third most common type of gynecological cancer in the country. [ 1 , 2 ] Vaccines against HPV types 16 and 18 are now available and can reduce the incidence of cervical and other anogenital cancers. [ 3 ] The HPV Working Group of the International Agency for Research on Cancer advised routine HPV vaccination for females aged 11 to 12 years in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%